A.K.A. Lucy : the dynamic and determined life of Lucille Ball - Royal, Sarah (Running Press, 2023)
An intimate and deeply original exploration of the life and work of the television pioneer, the First Lady of Comedy, Lucille Bal--A.K.A. Lucy. With stories illuminating the many different facets of the woman, [this book] details how Ball transformed the face of comedy and the entertainment industry. -- adapted from back cover